Dynamic Emission Reduction Strategy of New Energy Vehicles Based on Technology Investment Under Carbon Trading Policy - Lili Zhao; Jizi Li; Xiuli Bao (Energies)
In the context of carbon trading policy, carbon emissions in the supply chain of new energy vehicles have received much attention in academic research and practice. Consumer preference for environmental friendliness is also growing in new energy vehicle supply chain operations, which has prompted new energy vehicle manufacturers to invest in carbon abatement technologies to improve the environmental friendliness of new energy vehicles. At the same time, the increased demand for new energy vehicles will also increase the green promotion of third-party power battery recycling companies to facilitate the recycling of power batteries. Considering these special features in the new energy vehicle supply chain, we applied a differential game model to examine the carbon emission reduction behaviors and green promotion technologies of the new energy vehicle supply chain members from a long-term and dynamic perspective. Supply chain equilibrium strategies under four different scenarios were analyzed and compared, numerical experiments were conducted to validate the theoretical results, and sensitivity analyses were performed to identify further insights. The results of the study show that a unit carbon trading price reaching a critical threshold is a prerequisite for technical cooperation between the new energy vehicle manufacturer and the third-party power battery recycling company. It provides a theoretical basis for the government to set the carbon price, and it effectively stimulates the cooperation and emission reduction drive of new energy vehicle companies. The study breaks through the traditional cost–benefit framework, internalizes the carbon price as a supply chain cooperation drive, and opens up a new paradigm for new energy vehicle industry research.